2013
DOI: 10.1007/s10517-013-2011-x
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of Membrane-Receptor System of Blood Cells and Kidney Tissue in Experimental Diabetes Mellitus

Abstract: The effect of streptozotocin-induced diabetes mellitus on some parameters of energy metabolism and functional status of cell membranes was studied in experiments on rats. It was found that the development of diabetes mellitus is associated with dramatic changes in the metabolism of blood cells and kidney tissue: inhibition of aerobic ATP synthesis, accumulation of lactate, uncoupling of oxidative phosphorylation, and development of lactic acidosis. Diabetes mellitus leads to restructuring of membrane lipids, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…It has been observed that cellular membrane electrolyte transporter Na + -K + -ATPase dysfunction in diabetic subjects can be secondary to hyperglycemia [ 10 ]. Moreover, the functions of Ca 2+ -Mg 2+ -ATPase, Na + /Ca 2+ exchanger, and Ca 2+ pump, which are located in the cell membrane, mitochondria or endoplasmic reticulum, have been shown to be impaired in diabetes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that cellular membrane electrolyte transporter Na + -K + -ATPase dysfunction in diabetic subjects can be secondary to hyperglycemia [ 10 ]. Moreover, the functions of Ca 2+ -Mg 2+ -ATPase, Na + /Ca 2+ exchanger, and Ca 2+ pump, which are located in the cell membrane, mitochondria or endoplasmic reticulum, have been shown to be impaired in diabetes [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…NKA activity might impact SGLTs by providing the driving force for their activity [146]. In murine models of diabetes, changes in NKA function are probably due to high glycaemic levels [155][156][157]159] and impaired insulin signalling [158]. Nevertheless, the results' heterogeneity does not allow to clearly define the insulin effect on NKA.…”
Section: Summary Of Evidence and Discussionmentioning
confidence: 99%
“…In the renal cortex of murine STZ models, NKA activity was reported as increased [155][156][157] or as reduced due to impaired insulin binding to its receptor [158]. In two of those reports with increased NKA activity, insulin treatment reduced it [155,157].…”
Section: Glucose Effects On Renal Glucosementioning
confidence: 97%
“…And the functions of Ca 2+ -Mg 2+ -ATPase, Na + /Ca 2+ exchanger and Ca 2+ pump, which are located in cell membrane, mitochondria or endoplasmic reticulum, have been shown to be impaired in diabetes [40,41]. Electrolyte disturbances within cells can be induced by them above mentioned.…”
Section: Discussionmentioning
confidence: 99%